Features of managing complex technological systems in the nuclear energy sector in the context of national economic development - Hrinchenko, H. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2026)
The article examines the features of managing complex technological systems in nuclear power engineering under the conditions of national economic development. It is substantiated that nuclear power plants are multi-level socio-technical systems whose performance depends on the combined influence of economic, technical-technological, safety, and socio-organizational factors. The paper analyzes existing approaches to assessing the effectiveness of energy system management and identifies their limitations, particularly fragmentation and insufficient consideration of interdependencies between indicators. An integrated approach to evaluating management efficiency is proposed, based on the application of qualimetric assessment and the formation of an integral indicator. The method for assessing management efficiency is improved by incorporating four groups of factors: economic, technical-technological, safety, and socio-organizational. A management model for complex technological systems in nuclear energy is developed, taking into account the synergistic effect of factor interaction and incorporating feedback mechanisms. The proposed approach is tested through the calculation of an integral management efficiency indicator, which confirms its practical applicability and usefulness for decision-making support. The results obtained can be applied to improve management systems of energy enterprises and ensure the effective development of nuclear energy in the context of national economic transformation.